BUDAYA LOKAL DALAM TRADISI “NYUMPET” DI DESA SEKURO KECAMATAN MLONGGO KABUPATEN JEPARA - Widiana, Nurhuda (Da'wa and Communication Faculty State Islamic University Walisongo, Semarang, Indonesia, 2015)
Acculturation is a concept to describe the long process of confergence of two or more values which are owned by individual, group and society. The emergence of regention to new value system, must be understood as a part of love the society against old values (local). This is a process of learning to understand the new values is coming. In theses condition, isn’t appropriate to use claims of winning or losing, between Islam vis a vis the local culture. The view of Islam in society, will be strongly colored by its culture. So that, Islam will be have variant which suitable various with the heteroginas culture that exists in the society. This condition is being constantly will be occurring of up – down, whether Islam will be more colouring culture or otherwise the culture will be colouring of Islam. The tradition of “Nyumpet” in Sekuro village, into one small of example to explain the process of acculturation is running. In this where the preacher must be more prudently in the dealing with religious practice which banded in a local culture that still rooted in the society.***Akulturasi merupakan konsep untuk menggambarkan proses panjang bertemunya dua atau lebih tata nilai yang dimiliki individu, kelompok dan masyaraka. Munculnya penolakan terhadap tata nilai baru, harus dipahami sebagai bagian kecintaan masyarakat terhadap nilai-nilai lama (lokal). Hal ini merupakan proses belajar untuk memahami nilai-nilai baru yang datang. Pada kondisi seperti ini, tidak tepat digunakan klaim menang atau kalah, antara Islam vis a vis budaya lokal. Tampilan Islam di suatu masyarakat, akan sangat diwarnai oleh budaya yang dimilikinya. Sehingga Islam akan memiliki varian yang bermavam-macam sesuai dengan heteroginas budaya yang eksis di masyarakat. Kondisi ini secara terus-menerus akan mengalami pasang-surut, apakah Islam akan lebih mewarnai budaya atau sebaliknya budaya akan mewarnai Islam. Tradisi “Nyumpe”t di desa Sekuro, menjadi salah satu contoh kecil untuk menjelaskan proses akulturasi yang berjalan.Disinilah para da’I harus lebih bijaksana dalam menyikapi praktik keagamaan yang terbalut dalam budaya lokal yang masih mengakar di masyarakat.